2023
DOI: 10.1002/jmri.28797
|View full text |Cite
|
Sign up to set email alerts
|

Associations of MRI‐Derived Glymphatic System Impairment With Global White Matter Damage and Cognitive Impairment in Mild Traumatic Brain Injury: A DTI‐ALPS Study

Abstract: BackgroundAssessing the glymphatic function using diffusion tensor image analysis along the perivascular space (DTI‐ALPS) may be helpful for mild traumatic brain injury (mTBI) management.PurposeTo assess glymphatic function using DTI‐ALPS and its associations with global white matter damage and cognitive impairment in mTBI.Study TypeProspective.PopulationThirty‐four controls (44.1% female, mean age 49.2 years) and 58 mTBI subjects (43.1% female, mean age 48.7 years), including uncomplicated mTBI (N = 32) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…This has been pointed out in many papers. 68,80,81,88,160 This is discussed in section "Placement of ROI" with respect to various methods of solution.…”
Section: Controversy In Dti-alps Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This has been pointed out in many papers. 68,80,81,88,160 This is discussed in section "Placement of ROI" with respect to various methods of solution.…”
Section: Controversy In Dti-alps Methodsmentioning
confidence: 99%
“…In humans, several studies using the noninvasive ALPS method have reported abnormal ISF dynamics after TBI. [66][67][68] It has been reported that ALPS-index is decreased in the brain after TBI. 66,68 On the other hand, there are reports that ALPS-index is elevated in young patients with mild TBI.…”
Section: Application For Traumatic Brain Injurymentioning
confidence: 99%
See 2 more Smart Citations
“… 18 Previous studies have demonstrated the DTI‐ALPS index as a potential biomarker for glymphatic system function, with a lower value indicating reduced activity. 17 The DTI‐ALPS is not invasive and does not require gadolinium‐based contrast administration, which has been recently applied in AD, 17 PD, 19 mild traumatic brain injury, 20 and obstructive sleep apnea. 21 Most studies focused on the relationship between the ALPS index and cognition.…”
Section: Introductionmentioning
confidence: 99%